Gene and protein expression profiles of selected molecular targets mediating electrophysiological function in pgc-1-alpha deficient murine ventricles. (14th October 2021) - Saadeh, K; Chadda, K R; Ahmad, S; Valli, H; Nanthakumar, N; Fazmin, I T; Edling, C E; Huang, C L H; Jeevaratnam, K
Abstract: Background: The risk of cardiac arrhythmias increases significantly in patients with metabolic disorders such as obesity and diabetes mellitus. The mechanisms linking metabolic conditions and electrophysiological changes underlying cardiac arrhythmias remain poorly understood. Central to the energetic abnormalities characterising these conditions is mitochondrial dysfunction. Peroxisome proliferator activated receptor-γ (PPARγ) coactivator-1 (Pgc-1) regulate mitochondrial biogenesis and function. Their expression is impaired in metabolic disorders. Murine Pgc-1α−/− hearts replicate disrupted mitochondrial function and model the associated pro-arrhythmic electrophysiological abnormalities. Purpose: To explore the molecular mechanisms underlying the pro-arrhythmic electrophysiological changes in the Pgc-1α−/− murine model of mitochondrial dysfunction. Methods: Ventricular tissue samples were obtained from aged (>12 months) wild-type (WT) and homozygous Pgc-1α−/− mice. Quantitative PCR was used to examine transcription of 60 genes underlying cardiac tissue excitability, western blotting was used to examine expression of proteins relating to cardiac conduction velocity, and histological analysis was used to examine cardiac tissue fibrotic change. Results: qPCR analysis implicated downregulation of genes related to Na+-K+ ATPase activity (Atp1b1), surface Ca2+ entry (Cacna1c), action potential repolarisation (Kcnn1), autonomic function (Adra1d, Adcy4, Pde4d, Prkar2a), and morphological properties (Myh6, Tbx3) in murine Pgc-1α−/− ventricles. Western blotting revealed reduced NaV1.5 but normal Cx43 expression. Histological analysis revealed increased tissue fibrosis in the Pgc-1α−/− ventricles. Conclusions: These results identified molecular mechanisms underlying previously reported electrophysiological abnormalities such as impaired ventricular activation and reduced conduction velocity in arrhythmic substrate associated with Pgc-1 deficiencies. Results also correlated with earlier findings including functional effects of elevated Ca2+ concentrations. The present findings clarify possible mechanisms by which mitochondrial dysfunction affects electrophysiological function and identify potential pharmacological targets for anti-arrhythmic therapy. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Medical Research Council; the Wellcome Trust; British Heart Foundation